2021
DOI: 10.1177/13674935211024816
|View full text |Cite
|
Sign up to set email alerts
|

Validation of growth standards and growth references: A review of literature

Abstract: The World Health Organization (WHO) growth standards provide the most recognized and widely accepted way of assessing child growth. To ensure its applicability, accuracy, and reliability, studies have validated WHO growth standards against local populations and other internationally recognized growth references. We reviewed outcomes of evaluations done on WHO growth standards and assess the appropriateness of using these growth standards on a global level. We undertook a systematic quantitative review of studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…One of the major critiques of the MGRS has been that it does not stand the test of external validity as seen in a set of meta-analyses and studies attempting to validate the WHO-MGRS sample through large-scale national sample surveys. 6 In the context of India, external validation of the MGRS has been conducted by attempting Open access to identify a subsample from large-scale surveys such as the National Family Health Survey (NFHS) and Comprehensive National Nutrition Survey (CNNS) that might be close to the MGRS sample with regard to socioeconomic characteristics as well as feeding norms.…”
Section: Mgrs: External Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major critiques of the MGRS has been that it does not stand the test of external validity as seen in a set of meta-analyses and studies attempting to validate the WHO-MGRS sample through large-scale national sample surveys. 6 In the context of India, external validation of the MGRS has been conducted by attempting Open access to identify a subsample from large-scale surveys such as the National Family Health Survey (NFHS) and Comprehensive National Nutrition Survey (CNNS) that might be close to the MGRS sample with regard to socioeconomic characteristics as well as feeding norms.…”
Section: Mgrs: External Validitymentioning
confidence: 99%
“…3 ' These standards were considered appropriate for use globally, as they included samples from select countries from different parts of the world and studies found that children across the world grow similarly when their health and care needs are met. 3 Since the release of these standards, various attempts have been made at validating them in different country contexts (Sri Lanka, Indonesia, USA, etc) and some concerns have been raised about their universal applicability, [4][5][6] especially whether genetic factors are being sufficiently accounted for. India has been using these standards since 2008, both to determine…”
mentioning
confidence: 99%
“… 13 Amongst the literature analysed in a review of publications that validated WHO child growth standards globally, none presented similar growth trajectories as those estimated by WHO child growth standards. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Amongst the studies identified in a literature review of global validations of the WHO growth standards only one African study focused on children within the ages 0–5 years. 14 The WHO-Africa region has the highest prevalence of children with stunting and is amongst the most affected regions for nearly all forms of malnutrition. The aim of this study was to develop weight-for-age and height-for-age growth curves from the Zimbabwean 2018 National Nutrition Survey and compare these curves with the WHO growth standards to assess the applicability of the WHO child growth standards in evaluating nutrition outcomes of children in Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation